Snarl : in defense of stalled traffic and faulty networks - Miller, Ruth Austin; Michigan Publishing (University of Michigan) (University of Michigan Press, 2013)
It is possible to imagine a theory of democracy and a constitutional history independent of human subjectivity.
Keywords: Democracy : Philosophy; Communication and traffic : Political aspects; Transportation, Automotive : Political aspects; Constitutional law; Constitutional history